EXOGENOUS CERAMIDE INHIBITS SOME CANCER CELL LINES GROWTH, INDUCES APOPTOSIS, AND REDUCES MAMMARY ADENOCARCINOMA TUMORS IN MICE - Hassani, Hayfa H; Maleek, Muthana I; Yassen, Nahi Y (Al-Nahrain Journal of Science, 2018)
Fresh bovine brain and spinal cord samples were collected for separation ceramide. Tissues were homogenized with organic solvents to extract ceramide which purified by using silicic acid column and obtained one fraction with yellow color. Subsequently, the purified extract analyzed and identified by using TLC, spectrophotometer, infrared assay. The results confirmed that the purified extract was identified as ceramide in comparison with commercially standard ceramides. In addition, this work included several genetic and histopathological assays to demonstrate the antitumor activity of ceramide.It was found that 30 μg/ml of exogenous ceramide had antiproliferative activity against cancer cell lines (RD, Hep–2, AMN–3, and AMGM5) particularly against cancer cells model AMGM5; the percentage of growth inhibition was 80%. Moreover, ceramide was significantly induced apoptosis in cancer cell lines (RD, Hep–2, AMN–3, and AMGM5), the percentage of apoptotic cells was 18, 28, 30, and 50.3% respectively. Furthermore, histopathological study was carried out; it was found that administration of exogenous ceramide particularly at 250 mg/kg was revealed a putative regression of tumor growth and volume in adenocarcinoma mice.